Electrocatalytic reduction of CO2 with CCC-NHC pincer nickel complexes. Issue 68 (9th August 2017) - Cope, James D.; Liyanage, Nalaka P.; Kelley, Paul J.; Denny, Jason A.; Valente, Edward J.; Webster, Charles Edwin; Delcamp, Jared H.; Hollis, T. Keith
Abstract : CCC-NHC pincer Ni complexes electrocatalytically reduce CO2 to CO and formate at the first reduction potential without producing or requiring molecular H2 . Abstract : A CCC-NHC pincer Ni(ii )Cl complex was prepared according to the metallation/transmetallation methodology. It was fully characterized by electrochemical, NMR spectroscopic, theoretical, and X-ray crystallographic methods. The complex and its cation were evaluated for electrocatalytic reduction of CO2 under a variety of conditions and found to provide some of the fastest catalytic rates and highest substrate selectivities (CO2 vs. H + ) reported. Rates improved in the presence of water and, significantly, catalysis occurred at the first reduction potential, presumably at the Ni(i ) state. Controlled potential electrolysis (CPE) was found to yield CO at 34% and formate at 47% Faradaic efficiency (FE).